Pembiasaan Literasi Numerasi dan Hasil Belajar Matematika Kelas V MI Giwangretno - Oktaviana, Dewi; Murtopo, Bahrun Ali; Chamidi, Agus Salim (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
The purpose of this study was to determine the refraction of numeracy literacy for class V, mathematics learning outcomes for class V, and whether there is a relationship between numeracy literacy habituation and mathematics learning outcomes for class V MI. Sruweng Giwangretno The quantitative research method was used in this research, with the correlation method. As the research sample, 45 students from class V participated in this study. The data for this study came from numeracy literacy questionnaires and math story test questions given to class V students. The habituation of numeracy literacy in class V reached a criterion level of 91 %. The test results show the results of mathematics learning for class V students. The test results for learning mathematics for class V students show that the criteria level is good, 57.78 %. At a 5% significance level, the results of rxy = 0.41 are greater than r table = 0.2940 based on the product moment correlation test. This shows that the alternative hypothesis has been accepted. Based on the data analysis, it is possible to conclude that the habit of numeracy literacy has a relationship with it and affects students' mathematics learning outcomes.